Repeatable self-repairing microcapsule and preparation method thereof
By using cinnamic acid-polydimethylsiloxane as a self-healing agent in microcapsules and using light trigger for multiple repairs, the problems of single-use microcapsules repair effects and catalyst safety in the prior art have been solved, and the problem of in-depth research on the problem of microcapsules repair is achieved. Efficient, safe, and repeatable self-repair effect in complex environments.
Patent Information
- Application Number
- CN202411511189.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-20
AI Technical Summary
The repair effect of existing microcapsules is mainly one-time. The use of catalysts has the risk of safety and environmental pollution, and can only repair specific damage under specific conditions, making it difficult to widely use in complex environments.
Using cinnamic acid-polydimethylsiloxane as self-healing agent, microcapsules were prepared by prepolymer method, and the self-healing agent in the microcapsules were triggered for multiple repairs, avoiding the use of traditional catalysts and improving repair. Flexibility and security.
Repeatable self-repair under light conditions, reduce costs, improve the crack resistance and insulation stability of the material, and can be effectively repaired even if stored for more than 200 days, significantly improving the service life of the material.
Smart Images

Figure CN119158507A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-repairing insulating materials, and in particular relates to a microcapsule capable of repeated self-repairing and a preparation method thereof. Background Art
[0002] Polyurethane materials, as a high-performance polymer, are widely used as insulating materials in the field of electrical equipment due to their excellent environmental adaptability and wide application potential. The various excellent properties of polyurethane materials themselves, especially their oil resistance, are particularly outstanding. Even in an oily environment, polyurethane materials can maintain stable mechanical properties and insulation properties, and will not suffer performance degradation due to external oil erosion, thereby ensuring the stable operation of electrical equipment in complex environments. In order to meet the diverse needs of different electrical equipment for insulation material performance indicators, when preparing polyurethane materials, the physical and mechanical properties can be precisely controlled by adjusting the raw material composition and ratio. This flexibility enables polyurethane materials to better adapt to the application scenarios of various electrical equipment, improving the practicality and reliability of the materials.
[0003] However, during operation, electrical equipment is often affected by multiple factors such as continuous load, mechanical stress, long-term heating, and strong electric field. These factors work together to cause cracks on the surface or inside of the material, which in turn causes insulation failure. Insulation failure not only reduces the service life of electrical equipment, but may also pose a serious threat to operational safety. Therefore, how to improve the crack resistance and insulation stability of polyurethane materials has become an important issue in current research.
[0004] The self-healing ability of the biological world provides us with useful inspiration. Most natural systems, such as human skin and tissues, plant organs, and the bodies of marine animals, have repeatable self-repair mechanisms. This mechanism enables organisms to quickly restore damaged parts when repeatedly damaged by the outside world, thereby extending their lifespan. Drawing on this concept, if the repeatable self-healing ability is introduced into polyurethane insulation materials, the service life of the materials will be greatly improved. This is of great significance for realizing the intelligence of electrical equipment and extending its service life.
[0005] Self-healing materials can be divided into four types according to their repair mechanisms: external, internal, vascular network, and microcapsule. External self-repair requires an external stimulus to trigger the repair reaction, while internal self-repair does not require external stimulation and relies on the self-healing mechanism inside the material for repair. Vascular network self-repairing materials consist of a container network of self-healing materials connected by nodes. The liquid with self-healing ability contained in it can repair cracks under the surface of the material. Microcapsule self-repairing materials are filled with self-healing agents, which cause the capsule to rupture when cracks are formed, and release the self-healing agent to complete the repair.
[0006] The repair reaction itself is caused by a chemical reaction, and the enthalpy and energy of the reaction can be expressed by chain diffusion. During the repair process, the internal mechanism affects the Gibbs free energy, thereby affecting the healing efficiency. In the physical change, the components and microphase separation in the microcapsules play a role in repairing the damaged area of the composite material. The repair rate depends on many factors such as the properties of the repair material itself, temperature, and catalyst. By deeply studying the impact of these factors on the repair reaction, the performance of self-healing polyurethane materials can be further optimized and their reliability and durability in practical applications can be improved.
[0007] At present, the repair effect of microcapsules is mostly one-time, because the healing agent wrapped inside the capsule is often used to play a repair role. After the cracks are generated, the microcapsules rupture and the healing agent flows out to repair the gaps. This process will greatly reduce the healing agent. In addition, the released healing agent will become a hard solid, thus permanently losing its repair ability. These excess microcapsule matrix materials and healing agents will cause the insulation performance of the composite material to deteriorate, which is unacceptable but inevitable in industrial applications.
[0008] For external self-repair, the conditions that trigger the self-repair of microcapsules are very harsh. For example, some microcapsules require high temperatures for the repair reaction to occur, which will greatly reduce the stability of the insulating material; some reaction conditions require catalysts, and some enzyme catalysts are very sensitive to environmental conditions such as temperature, pH or pressure. If the catalyst loses its activity, the self-healing effect will be greatly reduced; some catalysts contain sulfides, which will be toxic and harmful to health during processing, and will also pollute the environment. At present, these catalysts can only catalyze one or one type of reaction, which means that this microcapsule only repairs a specific damage at a specific location. In addition, this repair method places higher requirements on material processing, so the cost will also be greatly increased.
[0009] For internal self-repair, it can only be used in a small part of composite insulation material systems and can only repair tiny volume damage. When faced with larger volume damage or more remote damage areas, its repair effect will be poor.
[0010] In view of the above-mentioned technical defects currently existing, the present invention designs an environmentally friendly microcapsule that can be repeatedly self-repaired. It does not use the traditional catalyst triggering method, but is triggered by natural light or in-situ ultraviolet rays emitted by the damaged material itself, and can repair damage in different locations. Summary of the invention
[0011] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0012] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0013] The invention synthesizes cinnamic acid-polydimethylsiloxane with self-repairing function under light conditions as a self-healing agent inside a microcapsule, and adopts a prepolymer method to prepare the shell of the microcapsule with toluene 2,4-diisocyanate and butanediol as main raw materials.
[0014] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a repeatable self-repairing microcapsule, wherein the microcapsule is a core-shell structure, wherein the core material is cinnamic acid-polydimethylsiloxane and the shell material is toluene diisocyanate prepolymer.
[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing microcapsules that are repeatable and self-repairable.
[0016] In order to solve the above technical problems, the present invention provides the following technical solutions, including:
[0017] Preparation of cinnamic acid-polydimethylsiloxane: dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine are stirred evenly to obtain solution A; dichloromethane is separately added dropwise into trans-cinnamoyl chloride in a nitrogen environment to react to obtain solution B; solution A and solution B are mixed and evaporated to reflux, and the obtained organic layer is washed, separated, dried, filtered and purified to obtain light yellow oily CA-PDMS;
[0018] Preparation of toluene diisocyanate prepolymer:
[0019] Toluene 2,4-diisocyanate is dissolved in cyclohexanone and suspended in an oil bath at 85°C, 1,4-butanediol is slowly added under continuous stirring; nitrogen is used for cleaning at the same time, and the reaction is carried out for 24 hours; then the mixture is distilled at 100°C for 5-6 hours to obtain a viscous toluene diisocyanate prepolymer;
[0020] Preparation of microcapsules:
[0021] After the toluene diisocyanate prepolymer is completely dissolved in chlorobenzene, isophorone diisocyanate and CA-PDMS are added in sequence, and the mixture is slowly poured into a 10% 25°C gum arabic solution; heating and stirring are continued, and after stirring at 80°C for 50 minutes, a polyurethane shell is formed at the interface between the water phase and the oil phase. After cooling to ambient temperature, the microcapsules are rinsed and vacuum filtered to obtain repeatable self-healing microcapsules;
[0022] When the mixture is heated and stirred to 50° C., a chain extender is slowly added.
[0023] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsule of the present invention, the method comprises: preparing cinnamic acid-polydimethylsiloxane: stirring dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine evenly to obtain solution A; taking dichloromethane and dropping trans-cinnamoyl chloride in a nitrogen environment to react to obtain solution B; mixing solution A and solution B and evaporating and refluxing to obtain an organic layer, washing, separating, drying, filtering and purifying to obtain a light yellow oily CA-PDMS;
[0024] Preparation of toluene diisocyanate prepolymer:
[0025] Toluene 2,4-diisocyanate is dissolved in cyclohexanone and suspended in an oil bath at 80-90°C, 1,4-butanediol is slowly added under continuous stirring; nitrogen is used for cleaning at the same time, and the reaction is carried out for 20-24 hours; then the mixture is distilled at 90-100°C for 5-6 hours to obtain a viscous toluene diisocyanate prepolymer;
[0026] Preparation of microcapsules:
[0027] After the toluene diisocyanate prepolymer is completely dissolved in chlorobenzene, isophorone diisocyanate and CA-PDMS are added in sequence, and the mixture is slowly poured into a surfactant at 20-30°C; heating and stirring are continued, and after stirring at 70-90°C for 40-60 minutes, a polyurethane shell is formed at the interface between the water phase and the oil phase. After cooling to ambient temperature, the microcapsules are rinsed and vacuum filtered to obtain repeatable self-healing microcapsules;
[0028] When the mixture is heated and stirred to 50-70° C., the chain extender is slowly added.
[0029] As a preferred solution of the method for preparing the repeatable self-repairing microcapsules of the present invention, the molar percentage of the aminopropylmethylsiloxane-dimethylsiloxane copolymer is 5-7%.
[0030] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass volume ratio of the dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine is 150 ml: 100 g: 8.11 g.
[0031] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass volume ratio of the dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine is 150ml:50-150g:8.11g.
[0032] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass volume ratio of the dichloromethane and trans-cinnamoyl chloride is 100 ml: 15.87 g.
[0033] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass volume ratio of the dichloromethane and trans-cinnamoyl chloride is 100 ml: 5-50 g.
[0034] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mixing volume ratio of the solution A and the solution B is 3:1-4.
[0035] As a preferred solution of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mixing volume ratio of the solution A and the solution B is 3:2.
[0036] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass ratio of toluene 2,4-diisocyanate, cyclohexanone and 1,4-butanediol is 20-25:160-170:5-6.
[0037] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass ratio of toluene 2,4-diisocyanate, cyclohexanone and 1,4-butanediol is 23.64:167.28:5.23.
[0038] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass ratio of the toluene diisocyanate prepolymer, chlorobenzene, isophorone diisocyanate, CA-PDMS and chain extender is 3:4:10:10-15:3-4.
[0039] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the mass ratio of the toluene diisocyanate prepolymer, chlorobenzene, isophorone diisocyanate, CA-PDMS and chain extender is 3:4:10:12.5:3.11.
[0040] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the heating and stirring comprises: the stirring rate is 500 to 1500 rpm, and the heating rate is 7 to 10°C / min.
[0041] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the heating and stirring comprises the following steps: the stirring rate is 500 to 1500 rpm, and the heating rate is 8°C / min.
[0042] As a preferred embodiment of the method for preparing the repeatable self-repairing microcapsules of the present invention, the chain extender includes one or more of 1,4-butanediol, ethylenediamine or N,N-dihydroxy(diisopropyl)aniline; and the surfactant includes gum arabic.
[0043] Beneficial effects of the present invention:
[0044] (1) The microcapsules prepared by the present invention can be repaired multiple times. The self-healing agent contained in the microcapsules is CA-PDMS, which has self-healing ability. When cracks appear in the composite material, the microcapsules rupture, and the cross-linked self-healing agent flows in a chain to fill the gaps. Viscoelastic cinnamoyl can be produced under light-triggered conditions, and the conversion rate can reach more than 90% after 5 hours. When secondary damage occurs, the substance acts like glue and can complete secondary repair.
[0045] (2) The triggering condition of the microcapsules prepared by the present invention is light, which reduces the cost and is more environmentally friendly compared to self-repairing microcapsules that require catalysts. The reaction efficiency is high, and the repair can be completed efficiently by adding low concentrations of microcapsules to the material. The degree of fusion between the healing agent and the matrix is good, which can better maintain the stability of the material's own performance, and the influence of doping on the intrinsic performance of the material can be ignored.
[0046] (3) Compared with other microcapsules, it has better mechanical properties, and a single microcapsule can bear a maximum load of 65mN. The incorporation of repeatable self-repairing microcapsules has a more obvious effect on insulation corrosion repair, and the repeatable self-repairing effect is not significantly weakened even after being stored for more than 200 days. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0048] Figure 1 The figure is a relationship diagram between the conversion rate of cinnamoyl obtained in Example 1 of the present invention and the light irradiation time.
[0049] Figure 2 The figure shows the morphological characteristics of the repeatable self-repairing microcapsules prepared in Example 1 of the present invention.
[0050] Figure 3 This is an optical photograph of the coating based on the repeatable self-repairing microcapsules prepared in Example 1 of the present invention being scratched for the first time.
[0051] Figure 4 This is an optical photograph of the first self-repair of the coating based on the repeatable self-repairing microcapsules prepared in Example 1 of the present invention after 48 hours.
[0052] Figure 5 This is an optical photograph of a coating based on the repeatable self-repairing microcapsules prepared in Example 1 of the present invention being scratched again after 48 hours.
[0053] Figure 6 This is an optical photograph of the coating based on the repeatable self-repairing microcapsules prepared in Example 1 of the present invention that repeatedly self-repaired after 96 hours.
[0054] Figure 7 It is the relationship between the storage days and the content of the repeatable repairing ingredients in the microcapsules.
[0055] Figure 8 Mechanical characterization of microcapsules prepared at different stirring speeds. DETAILED DESCRIPTION
[0056] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0057] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0058] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0059] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0060] Aminopropylmethylsiloxane-dimethylsiloxane copolymer was purchased from Beijing Anolun Biotechnology Co., Ltd., model AMS-162, with a molar percentage of 6%.
[0061] The raw materials and their abbreviations are as follows:
[0062] Cinnamic acid-polydimethylsiloxane (CA-PDMS), toluene diisocyanate (TDI), chlorobenzene (ClB),
[0063] After the microcapsules prepared in the embodiment of the present invention were air-dried for 48 hours, the performance test was performed as follows:
[0064] 1. Measurement of photoreaction conversion rate: CA-PDMS was coated on a glass slide and exposed to sunlight. The photoreaction conversion rate was measured by FT-IR spectroscopy, which can verify the photocrosslinking of CA-PDMS. The carbon-carbon double bond in cinnamoyl is in stretching vibration, which gradually decreases with the increase of exposure time. The calculated areas of the two absorption bands of the carbon-carbon double bond and the carbon-oxygen double bond were used as internal standards and compared with the ratio before exposure. The absorption beam of the carbon-oxygen double bond is 1659 cm -1 , to determine the degree of conversion of the cinnamoyl carbon-carbon double bond. -1 The carbonyl absorption band at 1648 cm was used as the internal standard for conversion determination (as the photoreaction proceeds, the band gradually changes to 1648 cm -1 .
[0065] 2. Characterization of prepolymer and microcapsules: The size of microcapsules was analyzed using a Leica optical microscope, Micropublisher CCD camera and image analysis software. 500 measurements were made and the average diameter and standard deviation were finally determined.
[0066] 3. Anticorrosion test results: The CA-PDMS-based coating and the control coating (a coating with the same parameters as the experimental sample except that it does not contain CA-PDM microcapsules) were applied to one side of the steel panel. Before coating, all steel substrates were washed with deionized water and acetone and dried under ambient conditions. The other side of the panel was painted with enamel paint. The size of the steel plate was 20mm*50mm*0.5mm. The coating was dried under ambient conditions for 5 days. Manual scribing was performed on the prepared self-healing and control coatings with a knife. The CA-PDMS-based coating and its control group were prepared, and the prepared coatings were irradiated for 4h respectively. The inscribed specimens were then immersed in 10% sodium chloride solution for 48h to evaluate the accelerated corrosion process. The coatings were washed with distilled water to remove the residual water, and the coatings were observed by optical photography. The initial inscribed and healing areas in the coating were re-inscribed and kept under ambient conditions for 1h. The second anticorrosion test was to immerse the coating in NaCl solution and then take photos as described above.
[0067] 4. Mechanical characterization results of microcapsules: The mechanical response of microcapsules was studied using a single capsule pressurization device. Displacement was applied at a rate of 1 μm / s using a stepper drive connected to the test device and controlled via a computer interface. Load data was collected from a 10 g weighing model TransducerTechniques GSO-10 sensor via a DAQ card and associated software from National Instruments, with a combined accuracy of ±100 nN for the sensor system. Images of the capsules during the compression cycle were captured by a monochrome CCD camera through a Nikon SMZ-2T stereo microscope. The entire system was mounted on a vibration isolation table. Before testing, the microcapsules were aspirated into a pipette so that a single capsule could be released onto the pressurization plate. Images of the microcapsules were taken before compression to determine the initial capsule diameter. The initial separation between the capsule and the punch allowed the stepper to reach a steady-state speed after the start of the motion. The test procedure was initiated after the punch was positioned above the capsule and terminated after the capsule rupture was observed.
[0068] Example 1
[0069] This embodiment provides a method for preparing microcapsules, specifically:
[0070] 1. Preparation of cinnamic acid-polydimethylsiloxane (CA-PDMS)
[0071] 150 ml of dry dichloromethane, 100 g of aminopropylmethylsiloxane-dimethylsiloxane copolymer and 8.11 g of triethylamine were stirred to form solution A. Another 100 ml of dry dichloromethane was added dropwise with 15.87 g of trans-cinnamoyl chloride in a nitrogen atmosphere to obtain solution B. Solution A and solution B were mixed and evaporated under reflux for 8 h. The organic layer was washed with NaOH solution, distilled water and saturated NaCl solution, separated, and Na 2 SO 4 After drying and removing the solvent under reduced pressure, the mixture was purified by filtration using gel ethyl acetate to obtain light yellow oily CA-PDMS.
[0072] 2. Preparation of toluene diisocyanate prepolymer
[0073] Toluene diisocyanate prepolymer was prepared as a component material for the microcapsule shell wall. 23.64 g of toluene 2,4-diisocyanate was dissolved in 167.28 g of cyclohexanone. The mixture was then suspended in an oil bath at 85°C and stirred with a magnetic stirrer. 5.23 g of 1,4-butanediol was slowly added. Purge with nitrogen and react for 24 hours. The mixture was then distilled at 100°C for 5.5 hours. Cyclohexanone, water and excess TDI were removed to a waste device, leaving a light yellow viscous prepolymer.
[0074] The average molecular weight of the prepolymer synthesized by gel permeation chromatography was 1310 and the average molecular weight was 1720. The polydispersity index (PDI) of the prepolymer was 1.41.
[0075] 3. Preparation of microcapsules by prepolymer method
[0076] In a 25°C water bath, 50 ml of distilled water and 5 g of gum arabic surfactant were mixed and stirred for 3 h. To prepare the microencapsulation solution, 3 g of toluene diisocyanate prepolymer was dissolved in 4.00 g of chlorobenzene (ClB) and the temperature was set to 75°C. Once the prepolymer was completely dissolved, 10.0 g of isophorone diisocyanate (IPDI) and 12.5 g of CA-PDM were added and mixed well. The mixture was then slowly poured into the gum arabic solution. The water bath was heated to 80°C at a rate of 8°C / min while stirring at a stirring rate of 900 rpm. At 60°C, 3.11 g of 1,4-butanediol was slowly added to the emulsion as a chain extender. After stirring for 50 min, stirring and heating were stopped. A polyurethane shell was formed at the interface between the water phase and the oil phase. After cooling to ambient temperature, the microcapsule suspension was rinsed with distilled water and vacuum filtered to obtain reproducible self-healing microcapsules.
[0077] Figure 1 The figure is a relationship between the conversion rate of cinnamoyl obtained in Example 1 of the present invention and the light irradiation time. It can be seen from the figure that after irradiation with LED light for 1, 2 and 6 hours, the cinnamoyl conversion rate of CA-PDMS is 22%, 43% and 94% respectively. On the other hand, after irradiation with sunlight for 6 hours, the conversion rate reaches 74%. It shows that both LED light and sunlight can stimulate CA-PDM to convert into viscoelastic cinnamoyl with secondary repair ability, among which the conversion efficiency of LED light is better than that of direct sunlight.
[0078] Figure 2 The morphological characterization of the reproducible self-healing microcapsules prepared in Example 1 of the present invention shows that most of the microcapsules are spherical under a microscope, and occasionally some elongated (ellipsoidal) shapes appear, which is caused by the low stirring rate. The outer surface of the capsule is relatively smooth, with some wrinkles due to the interaction of uneven reaction dynamics, fluid-induced shear force and elastic force determined by the shell. The inner surface is usually smoother because the shear flow inside the capsule is very small during the formation of the shell wall.
[0079] According to the experimental results, all control samples were corroded, but the self-healing coating showed no obvious signs of corrosion. The scratched area in the self-healing coating was scratched a second time to evaluate its repeatable self-healing ability. The coating samples were immersed in the NaCl solution again for 48 hours. It was found that the control coating corroded further. Figures 3 to 6, it can be seen that, obviously, despite the secondary damage, the CA-PDMS coating has almost no corrosion. The cross-linked CA-PDMS has viscoelastic properties and can therefore self-heal repeatedly. This result clearly demonstrates the repeatable self-healing ability of the CA-PDMS coating system.
[0080] The shelf life of CA-PDMS filled microcapsules produced at 900 rpm was investigated by TGA experiments. The capsules were stored in sealed glass bottles at room temperature for 100 and 200 days and then analyzed by TGA to observe compositional changes. After 100 and 200 days of storage at ambient temperature, the CA-PDMS core material decreased by 7.9 wt.% and 8.6 wt.%, respectively. The decrease in CA-PDMS core content was equivalent to the subsequent increase in shell wall material, indicating that some CA-PDMS reacted slowly with the diffused water to form new shell wall material, such as Figure 7 Furthermore, the encapsulated CA-PDMS released from the ruptured capsule between the two glass slides continued to show good reactivity when in contact with the shell, thus bonding the glass slides tightly.
[0081] Example 2
[0082] The difference between this embodiment and embodiment 1 is that the stirring rate is adjusted to 500 rpm, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0083] Example 3
[0084] The difference between this embodiment and embodiment 1 is that the stirring rate is adjusted to 700 rpm, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 1 is that the stirring rate is adjusted to 1100 rpm, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that the stirring rate is adjusted to 1500 rpm, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0089] Comparative Example 1
[0090] The difference between this comparative example and Example 1 is that the stirring rate is adjusted to 300 rpm, and the rest of the preparation process is the same as that of Example 1 to prepare microcapsules.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 1 is that the stirring rate is adjusted to 1700 rpm, and the rest of the preparation process is the same as that of Example 1 to prepare microcapsules.
[0093] The performance of the materials prepared in the above examples and comparisons was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0094] Table 1
[0095]
[0096] In the stirring rate range of 500-1500 rpm, the average yield of microcapsules is about 76%. Figure 8 It can be seen that the load strength that the microcapsules can withstand increases linearly with the applied load until a maximum value is reached. Larger capsules withstand higher loads before rupture due to their thicker shell walls. The stirring rate is inversely proportional to the diameter of the microcapsules: the average diameter of the microcapsules produced at 500 rpm is 240 μm, while the average diameter of the microcapsules produced at 1500 rpm is 38 μm. The records of the compression tests confirmed that the failure rupture of the microcapsules coincided with the maximum load. After failure, the encapsulated healing agent was released from the microcapsules. According to the calculation formula of the maximum strength, the maximum strength σ max It is inversely proportional to the difference between the outer diameter and the inner diameter of the capsule. Therefore, when other conditions are the same, the larger the diameter of the microcapsule, the greater its maximum strength.
[0097] Microcapsules synthesized at different stirring rates all have similar thermal properties. The release of the core material (CA-PDMS) in the microcapsules occurs at higher temperatures compared to the unencapsulated components. For all capsules, the mass loss before 110°C was less than 3%, indicating that only a small amount of water was adsorbed on the surface of the microcapsules. The mass loss at 120°C is associated with the onset of diffusion of the CA-PDMS contained within the microcapsules. The mass loss peak at 250°C indicates that the CA-PDMS has evaporated. The final mass loss is associated with the decomposition of the shell wall, and the decomposition of all microcapsule batches overlaps, indicating that there is no remaining CA-PDMS above 280°C.
[0098] According to the results in the above table, the best technical effect can be obtained when the stirring rate in the present invention is 900 rpm.
[0099] Example 6
[0100] The difference between this embodiment and embodiment 1 is that the preparation temperature of the microcapsules is adjusted to 50° C., and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0101] Example 7
[0102] The difference between this embodiment and embodiment 1 is that the preparation temperature of the microcapsules is adjusted to 70° C., and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0103] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0104] Table 1
[0105]
[0106] It can be seen from the above table that adjusting the temperature during the preparation process has a significant effect on the performance of the microcapsules. This is because if the preparation temperature is too high, the thermal mass loss of the microcapsules will be aggravated and the effective content of CA-PDM will be reduced; if the preparation temperature is too low, the reaction will be insufficient and the load-bearing capacity of the microcapsule shell will decrease. According to the results in the above table, the best technical effect can be obtained when the preparation temperature in the present invention is 60°C.
[0107] Example 8
[0108] The difference between this embodiment and embodiment 1 is that the amount of aminopropylmethylsiloxane-dimethylsiloxane copolymer used in the preparation of CA-PDMS is adjusted to 50 g, and the rest of the preparation process is the same as that of embodiment 1 to obtain microcapsules.
[0109] Example 9
[0110] The difference between this embodiment and embodiment 1 is that the amount of aminopropylmethylsiloxane-dimethylsiloxane copolymer used in the preparation of CA-PDMS is adjusted to 150 g, and the rest of the preparation process is the same as that of embodiment 1 to obtain microcapsules.
[0111] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.
[0112] Table 2
[0113]
[0114] It can be seen from the above table that adjusting the amount of aminopropyl methylsiloxane-dimethylsiloxane copolymer has a significant effect on the performance of the microcapsule. This is because if too little of this substance is added, the effective content of CA-PDMS will be reduced, and the thermal mass loss will be aggravated; if too much of this substance is added, it will be an impurity that has not fully reacted in the microcapsule. Adding too much or too little of this substance will affect the repair effect of the microcapsule. According to the results in the above table, the best technical effect can be obtained when the amount of aminopropyl methylsiloxane-dimethylsiloxane copolymer in the present invention is 100g.
[0115] Example 10
[0116] The difference between this embodiment and embodiment 1 is that the amount of trans-cinnamoyl chloride used to prepare CA-PDMS is adjusted to 5 g, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0117] Embodiment 11
[0118] The difference between this embodiment and embodiment 1 is that the amount of trans-cinnamoyl chloride used to prepare CA-PDMS is adjusted to 50 g, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.
[0119] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.
[0120] Table 3
[0121]
[0122] It can be seen from the above table that adjusting the amount of trans-cinnamoyl chloride has a significant effect on the performance of the microcapsule. This is because if too little trans-cinnamoyl chloride is added, the CA-PDM content in the microcapsule will be reduced, and the heat loss of the microcapsule will be more serious; if too much of this substance is added, this impurity will be contained in the microcapsule core material. Adding too much or too little of this substance will affect the repair effect of the microcapsule. According to the results in the above table, the trans-cinnamoyl chloride in the present invention can achieve the best technical effect when the amount is 15.87g.
[0123] Comparative Example 3
[0124] 17.5g of gum arabic emulsifier was added to distilled water and mechanically stirred until it was clear. Polyurethane, isophorone diisocyanate and ethyl acetate were added to the emulsifier aqueous solution at room temperature, and placed in a flask under a nitrogen environment. After stirring until uniform, the mixture was reacted in a 55°C constant temperature water bath for 1 hour, and then cooled to room temperature and separated by precipitation. The precipitate was washed three times with distilled water, dried in air, and finally stored in a dryer to obtain an insulating polyurethane material.
[0125] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 4.
[0126] Table 4
[0127]
[0128] It can be seen from the above table that, compared with the existing method, the fusion degree between the microcapsules prepared by the present invention and the matrix is slightly improved, the maximum mechanical load that can be sustained is slightly improved, and the repair result can be guaranteed for a longer time.
[0129] In summary, the microcapsules prepared by the present invention can be repaired multiple times. The self-healing agent contained in the microcapsules is dimethylsiloxane, which has self-healing ability. When cracks appear in the composite material, the microcapsules break, and the cross-linked self-healing agent flows in a chain to fill the gaps. Viscoelastic cinnamoyl can be produced under light triggering conditions, and the conversion rate can reach more than 90% after 5 hours. When secondary damage occurs, the substance plays a role similar to glue and can complete secondary repair. The triggering condition of the microcapsules prepared by the present invention is light, which reduces the cost and is more environmentally friendly compared to self-healing microcapsules that require catalysts. The reaction efficiency is high, and the repair can be efficiently completed by adding a low concentration of microcapsules to the material. The degree of fusion between the healing agent and the matrix is good, which can better maintain the stability of the material's own performance, and the effect of doping on the intrinsic performance of the material can be ignored. Compared with other microcapsules, it has better mechanical properties, and a single microcapsule can bear a maximum load of 65mN. The incorporation of repeatable self-repairing microcapsules has a more obvious effect on the repair of insulation corrosion, and the repeatable self-repairing effect is not significantly weakened even after being stored for more than 200 days.
[0130] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A microcapsule capable of repeated self-repair, characterized in that: The microcapsule is a core-shell structure, wherein the core material is cinnamic acid-polydimethylsiloxane and the shell material is toluene diisocyanate prepolymer.
2. The method for preparing the repeatable self-repairing microcapsule according to claim 1, characterized in that: include, Preparation of cinnamic acid-polydimethylsiloxane: dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine are stirred evenly to obtain solution A; dichloromethane is separately added dropwise into trans-cinnamoyl chloride in a nitrogen environment to react to obtain solution B; solution A and solution B are mixed and evaporated to reflux, and the obtained organic layer is washed, separated, dried, filtered and purified to obtain light yellow oily CA-PDMS; Preparation of toluene diisocyanate prepolymer: Toluene 2,4-diisocyanate is dissolved in cyclohexanone and suspended in an oil bath at 80-90°C, 1,4-butanediol is slowly added under continuous stirring; nitrogen is used for cleaning at the same time, and the reaction is carried out for 20-24 hours; then the mixture is distilled at 90-100°C for 5-6 hours to obtain a viscous toluene diisocyanate prepolymer; Preparation of microcapsules: After the toluene diisocyanate prepolymer is completely dissolved in chlorobenzene, isophorone diisocyanate and CA-PDMS are added in sequence, and the mixture is slowly poured into a surfactant at 20-30°C; heating and stirring are continued, and after stirring at 70-90°C for 40-60 minutes, a polyurethane shell is formed at the interface between the water phase and the oil phase. After cooling to ambient temperature, the microcapsules are rinsed and vacuum filtered to obtain repeatable self-healing microcapsules; When the mixture is heated and stirred to 50-70° C., the chain extender is slowly added.
3. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The molar percentage of the aminopropylmethylsiloxane-dimethylsiloxane copolymer is 5-7%.
4. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The mass volume ratio of the dichloromethane, aminopropylmethylsiloxane-dimethylsiloxane copolymer and triethylamine is 150ml:50-150g:8.11g.
5. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The mass volume ratio of the dichloromethane and trans-cinnamoyl chloride is 100 ml: 5-50 g.
6. The method for preparing the repeatable self-repairing microcapsule according to claim 2, 4 or 5, characterized in that: The mixing volume ratio of the solution A to the solution B is 3:1-4.
7. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The mass ratio of toluene 2,4-diisocyanate, cyclohexanone and 1,4-butanediol is 20-25:160-170:5-6.
8. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The mass ratio of the toluene diisocyanate prepolymer, chlorobenzene, isophorone diisocyanate, CA-PDMS and chain extender is 3:4:10:10-15:3-4.
9. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The heating and stirring, wherein the stirring rate is 500-1500 rpm, and the heating temperature rising rate is 7-10° C. / min.
10. The method for preparing the repeatable self-repairing microcapsule according to claim 2, characterized in that: The chain extender includes one or more of 1,4-butanediol, ethylenediamine or N,N-dihydroxy(diisopropyl)aniline; and the surfactant includes gum arabic.
